Oxford Handbook of industrial archaeology - Casella, Eleanor Conlin; Nevell, Michael; Steyne, Hanna (United Kingdom : Cambridge University Press, 2022)
"Representing the first substantial English-language text on Industrial Archaeology in a decade, this volume comes at a time when the global impact of industrialisation is being re-assessed in terms of its legacy of climate change, mechanisation, urbanisation, the forced migration of peoples, particularly enslaved Africans, and labour relations. Critical debates around the beginning of a new geological era - The Anthropocene - have emerged over the last decade. This approach interrogates the widespread exploitation of natural resources that forged industrialisation from its early emergence in 18th century northern Europe to its contemporary ubiquity, environmental impacts, and social legacy within our globalised world. Through a broad international and multi-period set of chapters, this volume explores the complex origins, processes, and development of industrialisation through both its physical remains and human consequences - both the good and the bad. It provides a diverse material framework for understanding our modern world from its industrial origins through its future paths over the third decade of the 21st century"--
Keywords: Industrial archaeology -- Handbooks, manuals, etc